Technological capabilities assessment by using Technometrics models in routine maintenance of commuter trains to increase service performance - Franka Hendra Sukma; Estiningsih Tri Handayani; Supriyono Supriyono (Universitas Mercu Buana, 2023)
Based on data on routine maintenance records for Indonesian Commuter Trains from 2015 - 2017, it is known that the number of realized train availability levels is still below the company’s standards and targets. In addition, there is a potential risk of a backlog or train queues that are not handled properly in overhaul maintenance which is increasing yearly. The main objective of this research is to measure the technological capability of the routine maintenance of the Indonesian Commuter Train which is located at Dipo Depok. The method used in this paper is the Technometrics model approach which will produce a Technology Contribution Coefficient (TCC) value. The method describes the level of technology applied by routine maintenance of TCC obtained by identifying and assessing the technological components of Technoware (tool facilities), Humanware (HR), Infoware (information), and Orgaware (organization) involved in the routine maintenance operation process of commuter trains by measuring the Degree of Sophistication, State of the Art (SOTA) and Contribution Assessment, as well as the intensity of the contribution of technology components using an Analytical Hierarchy Process (AHP). The results of this study identified 11 operating processes in maintenance activities. The SOTA values are T = 0.3857, H = 0.7750, I = 0.7111 and O = 0.633, with the contribution value being 0.4190, 0.6059, 0.5667 and 0.5862, and the contribution intensity is 0.301, 0.438, 0.132 and 0.030. Therefore, the TCC value for routine maintenance of Indonesian Commuter Trains with a value of 0.5 (TCC 0.3 ≤ TCC≤ 0.5) is categorized as low. With these results, the priority order of technology component development is humanware, technology, orgaware and infoware.